“If there is a risk, I should have a choice:” Risk management and risk perception in Italian vaccine hesitancy movements - Valentina Sbocchia (Salud Colectiva, 2021)
In Italy, the passing of mandatory pediatric vaccinations in 2017 was a consequence of increasing vaccine hesitancy in the country, a phenomenon that has largely spread on social networks. This article examines risk management and risk perception regarding pediatric vaccinations through an analysis of online content shared by Italian vaccine hesitancy movements between December of 2019 and April of 2020. Results show that these movements carry out a reinterpretation of risk, scientific evidence, and parental responsibility, especially with regard to the alleged correlation between the measles vaccine and autism. The limitations of political decisions surrounding vaccines are due to the application of punitive measures such as administrative penalties and licensing bans for doctors who express “anti-vax” ideas, aspects which may increase distrust towards the political establishment and the medical profession.